2009
DOI: 10.1063/1.3176516
|View full text |Cite
|
Sign up to set email alerts
|

A nonextensive approach for the instability of current-driven ion-acoustic waves in space plasmas

Abstract: The instability of current-driven ion-acoustic waves in the collisionless magnetic-field-free space plasma is investigated by using a nonextensive approach. The ions and the electrons are thought of in the power-law distributions that can be described by the generalized q-Maxwellian velocity distribution and are considered with the different nonextensive q-parameters. The generalized q-wave frequency and the generalized instability q-growth rate for the ion-acoustic waves are derived. The numerical results sho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 109 publications
(57 citation statements)
references
References 21 publications
1
56
0
Order By: Relevance
“…There are two separate physical regions, −1 < q 1, covering all velocities (and potentially representing highenergy tails) and q 1, where the distribution function exhibits a thermal cut-off on the maximum value allowed for the velocity of the particles [17,18]. In recent years, this Tsallis model has frequently been used for investigations into ion acoustic dynamics in plasmas [19][20][21][22][23][24][25][26]. Using a pseudopotential approach, Dubinova and Dubinov [19] studied the dependence of the Mach number of ion acoustic solitons on the parameter q. Tribeche et al [22] considered ion acoustic solitary wave generation in a two-component plasma with Tsallis-distributed electrons and found that their model allowed for both compressive and rarefactive solitons to arise.…”
Section: Introductionmentioning
confidence: 99%
“…There are two separate physical regions, −1 < q 1, covering all velocities (and potentially representing highenergy tails) and q 1, where the distribution function exhibits a thermal cut-off on the maximum value allowed for the velocity of the particles [17,18]. In recent years, this Tsallis model has frequently been used for investigations into ion acoustic dynamics in plasmas [19][20][21][22][23][24][25][26]. Using a pseudopotential approach, Dubinova and Dubinov [19] studied the dependence of the Mach number of ion acoustic solitons on the parameter q. Tribeche et al [22] considered ion acoustic solitary wave generation in a two-component plasma with Tsallis-distributed electrons and found that their model allowed for both compressive and rarefactive solitons to arise.…”
Section: Introductionmentioning
confidence: 99%
“…The physical explanation for the parameter q different from unity was represented for the nonequilibrium plasma system with Coulombian long-range interactions 19 . Many of the basic characteristics of electron-ion plasmas and dusty plasmas have been investigated under the condition of the power-law q-distributions, such as electron and ion dust charging process 26 , ion acoustic waves [27][28][29][30][31][32][33] , dust acoustic waves [34][35][36][37] , solitary waves 29,[36][37][38] , electron acoustic waves [39][40][41] , and Jeans' instability in space plasma 42,43 , etc. Nevertheless, according to present knowledge, the usually employed q-distribution function is not factorized for kinetic and potential energies because without considering the nonextensivity of the energy.…”
Section: Introductionmentioning
confidence: 99%
“…Eq. (4) has also be applied to establish new characteristics in the nonequlibrium space plasmas with the power-law distributions [17,18,50,51]. In this work, on the basis of the q-kinetic theory in NSM we will study the q-parameter for the rotating astrophysical systems with the q-distribution, generally including the self-gravitating systems and the space plasmas.…”
Section: -----------------------------------------mentioning
confidence: 99%